Synthesis and characterization of fluorous-stabilized metal nanoparticles for evaluation in fluorous biphasic catalysis - Hensberg, Joshua (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.